DRIS para a cultura da bananeira na região norte do Paraná - Diorio, Carlos Alberto (2012)
The aim of this study was to establish norms of the Diagnosis and Recommendation Integrated System (DRIS) in the culture of banana (Musa sp) for the subgroup Cavendish. We used 107 leaf samples from plants on farms in the towns of Andirá and Rancho Alegre, both located in Northern Paraná State, cultivars Nanicão and Grande Naine , with and without irrigation, aged 2 to 10 years. Chemical analysis determined the content of leaf 11 nutrients N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn. DRIS norms have been established for less than average productivity of 75 t ha-1, where it was found differences between the patterns of levels of nutrients and DRIS norms developed in this study. It was recommended the need for reprogramming of the quantities of fertilizer to be used according to the results obtained for the N, Ca, Mg, S, Fe and Zn contents presenting below the pre-established standards tracks.